SEBAB PERCERAIAN YANG DIPICU PERTENGKARAN KARENA MASALAH UTANG DI BANK EMOK (STUDI KASUS DI DESA TANJUNGSARI KECAMATAN SALOPA KABUPATEN TASIKMALAYA) - Ipin Tajul Aripin; Lukmanul Hakim; Siti Puadah (Program Studi Hukum Keluarga Islam, 2023)
The inception of the debt and credit system at Emok Bank in Tanjungsari Village, Salopa Subdistrict, Tasikmalaya Regency is closely linked to the inadequate income generated for meeting household need. Nevertheless, the provision of loans to bank personnel is accompanied by numerous detrimental repercussions in practical application. The primary objective of this research is to ascertain the viewpoints of Islamic law and positive law on bank emok, discern the factors that contribute to the emergence of bank emok, and analyze the societal ramifications associated with bank emok. The present study employs a qualitative descriptive methodology, with the objective of offering a full depiction of the observed occurrences. The research employed a normative-empirical methodology, adopting a juridical perspective. The acquisition of primary and secondary data was facilitated through the utilization of observation, interviews, and literature research as methods of data collecting. The findings of this analysis suggest that the debt and credit transactions conducted at Bank Emok fall within the realm of muamalah actions that are prohibited according to Islamic law. The presence of usury is a notable factor in the execution of these agreements. Furthermore, within the domain of positive law, there exists a lack of precise norms governing this particular issue. The proliferation of these loans is contingent upon prevailing economic circumstances and the adoption of a hedonistic way of life. Moreover, this phenomenon has had an impact on the frequency of divorce. The establishment of the debt and credit system at Emok Bank in Tanjungsari Village, Salopa Subdistrict, Tasikmalaya Regency is intricately connected to the insufficiency of money generated to fulfill household need. However, the act of providing loans to bank employees is associated with several negative consequences in real-world implementation. The main aim of this study is to investigate the perspectives of Islamic law and positive law about bank emok, identify the reasons that contribute to the establishment of bank emok, and examine the societal consequences associated with bank emok. The current study utilizes a qualitative descriptive methodology in order to provide a comprehensive portrayal of the observed phenomena. The study utilized a normativeempirical approach, taking into consideration a juridical standpoint. The collection of primary and secondary data was aided by employing observation, interviews, and literature research as data collection methods. The research reveals that the debt and credit transactions carried out by Bank Emok are deemed impermissible under Islamic law, as they fall within the category of muamalah actions that are prohibited. The existence of usury is a significant element in the implementation of these agreements. Moreover, it is worth noting that within the realm of positive law, there is a noticeable absence of well-defined rules that regulate this specific matter. The widespread availability of these loans is dependent on the current economic conditions and the acceptance of a hedonistic lifestyle. Furthermore, this phenomena has had a significant influence on the prevalence of divorce